2012
DOI: 10.1177/147323001204000244
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Predictive Power of the LODS and APACHE II Scoring Systems in a Neurological Intensive Care Unit

Abstract: OBJECTIVE:A prospective study to compare the power of the Logistic Organ Dysfunction System (LODS) and the Acute Physiology and Chronic Health Evaluation II (APACHE II) scoring systems to predict survival, in patients admitted to the neurological intensive care unit (NICU). METHODS: Clinical data from 521 consecutive NICU patients were collected during the first 24 h of admission and were used to compare the predictive power of both scoring systems. RESULTS: The observed mortality rate was 10.0% compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 33 publications
(29 reference statements)
0
5
0
1
Order By: Relevance
“…Another prospective study by Kim and Yoon in 521 consecutive patients admitted to the neurological ICU, showed that both the LODS and the APACHE II score had excellent discrimination but LODS had superior calibration; they therefore, concluded that the LODS was more stable than the APACHE II scoring system in the neurological ICU setting. [30] However, Maccariello et al . [7] evaluated the performance of LODS in patients receiving renal replacement therapy and found poor correlation between LODS score and predicted mortality rate.…”
Section: Types Of Icu Scoring Systemsmentioning
confidence: 99%
“…Another prospective study by Kim and Yoon in 521 consecutive patients admitted to the neurological ICU, showed that both the LODS and the APACHE II score had excellent discrimination but LODS had superior calibration; they therefore, concluded that the LODS was more stable than the APACHE II scoring system in the neurological ICU setting. [30] However, Maccariello et al . [7] evaluated the performance of LODS in patients receiving renal replacement therapy and found poor correlation between LODS score and predicted mortality rate.…”
Section: Types Of Icu Scoring Systemsmentioning
confidence: 99%
“…The APACHE II scoring system is now widely applied for evaluating the severity of illness and the prognosis of ICU patients. However, the score is somewhat related to the management in ICU because the worst score within 24 h rather than the score upon admission is required (Ho et al, 2006), and it is not stable for evaluating the severity of illness and the prognosis of neonatal intensive care patients (Kim and Yoon, 2012). Therefore, its application in this study has some limitations.…”
Section: Discussionmentioning
confidence: 97%
“…Six sub-score ranged from 0–5 for LODS, developed by Le Gall et al in 1996 [ 30 ]. Previous prediction of outcomes in neurological ICU patients have shown that LODS has more stability than APACHE II [ 31 ]. However, we found that our nomogram was more superior to the LODS score, which accounts for the largest proportion of the nervous system.…”
Section: Discussionmentioning
confidence: 99%